An improved experimental-theoretical method for calculating the particle trajectory in a pneumatic separating channel - A. I. Burkov; A. L. Glushkov; V. A. Lazykm (Аграрная наука Евро-Северо-Востока, 2018)
The article presents an improved experimental-theoretical method for calculating the particle trajectory in a pneumatic separating channel. Mathematic simulation of the velocity field of the air flow in the longitudinal-vertical plane of the pneumatic separating channel is made on the basis of measuring their actual magnitude and direction at the nominal grain load. Calculation and construction of particle trajectories is performed with regard to their ricochet from the channel walls. The improved method includes three stages. At the first stage, the vector field of airflow velocity in equal rectangular centers located in the separation area throughout the height and depth of the pneumatic separating channel are determined experimentally. At the second stage, on the basis of particular values of velocity vectors in the rectangular centers the systems of math equations are made. They describe the vertical and horizontal components of these velocities in the corresponding sectors of coordinate axes. At the third stage, the system of differential equations of particle motion in a pneumatic separating channel relative to a Cartesian coordinate system is made and their trajectories are calculated. This improved method raises the accuracy of calculation the particle trajectory inside the pneumatic separating channel and aerodynamic parameters of particles when leaving it. It results in speeding up the process of optimization of the design parameters of the channel and the attached elements of the pneumatic system.